Laboratory investigation of the effect of sodium silicate and bentonite on the mechanical properties of the grout behind the segment in mechanized excavation (Rudarsko-geološko-naftni zbornik, 2024)
Nowadays, the use of Tunnel Boring Machines (TBM) in tunnelling has increased in urban environments. One of the effective parameters in the excavation process is the use of grout behind the segments to prevent ground settlement and penetration into the tunnel. The investigation of the effects of two-component grout (bentonite and sodium silicate) on the mechanical properties of the grout plays a crucial role in mechanized excavation. Therefore, this article aims to investigate the effect of various parameters on the properties of the two-component grout. Eight different mixing designs were considered in this research. Gel-time tests, viscosity test, water bleeding test, uniaxial compressive strength tests (UCS), and direct shear tests were conducted for each mixing design. The UCS tests were performed for eight mixing designs and at four different ages of the grout, while the direct shear test was conducted for five mixing designs at the age of one day. The results showed that increasing the sodium silicate content from 4% to 9.4% reduced the Gel-time to 7 seconds, and increasing the bentonite content from 2.3% to 4.58%, increased the marsh funnel time to 12 seconds. The uniaxial compressive strength of the grout increased to 0.682 MPa at the age of 28 days. Finally, by conducting the direct shear test on the grout and obtaining the parameters of cohesion and internal friction angle, it was determined that these two parameters depend on the values of bentonite and sodium silicate, and they change with the increase or decrease of these grout components.